Commentary: Creating Hybrid After-School Enrichment Activities (LEARNing Landscapes, 2012)
In this commentary we propose a collaborative strategy for the creation of informal learning activities in after-school settings that are also shared sites of learning, research, and development. We briefly trace the history of a research program—"UCLinks"—whose defining feature is a form of collaboration between institutions of higher learning and local community institutions responsible for youth in the afterschool hours. These collaborations thrive only to the degree that "mutual appropriation" can be negotiated between partners, and it is within mutual appropriation that new possibilities for creative cross-generational and cross-cultural informal learning activities are materialized.
Keywords: informal learning; after-school setting; learning; research; development; collaboration